Ventral striatum regulates behavioral response to ethanol and MDMA combination. (14th July 2020) - Ben Hamida, Sami; Lecourtier, Lucas; Loureiro, Michaël; Cosquer, Brigitte; Tracqui, Antoine; Simmoneaux, Valérie; Nehlig, Astrid; Jones, Byron C.; Pereira de Vasconcelos, Anne; Cassel, Jean‐Christophe
Abstract: Our previous studies consistently showed that MDMA‐induced locomotor hyperactivity is dramatically increased by coadministration of ethanol (EtOH) in rats, indicating possible potentiation of MDMA abuse liability. Thus, we aimed to identify the brain region(s) and neuropharmacological substrates involved in the pharmacodynamics of this potentiation. We first showed that potentiation of locomotor activity by the combination of ip administration of EtOH (1.5 g/kg) and MDMA (6.6 mg/kg) is delay sensitive and maximal when both drugs are injected simultaneously. Then, we used the 2‐deoxyglucose quantitative autoradiography technique to assess the impact of EtOH, MDMA, or their combination on local cerebral metabolic rates for glucose (CMRglcs). We showed a specific metabolic activation in the ventral striatum (VS) under MDMA + EtOH versus MDMA or EtOH alone. We next tested if reversible (tetrodotoxin, TTX) or permanent (6‐hydrodoxyopamine, 6‐OHDA) lesion of the VS could affect locomotor response to MDMA and MDMA + EtOH. Finally, we blocked dopamine D1 or glutamate NMDA receptors in the VS and measured the effects of MDMA and MDMA + EtOH on locomotor activity. We showed that bilateral reversible inactivation (TTX) or permanent lesion (6‐OHDA) of the VS prevented the potentiation by EtOH of MDMA‐induced locomotor hyperactivity. Likewise, blockade of D1 or NMDA receptors in the VS also reduced the potentiation of MDMA locomotor activity by EtOH. These data indicate that dopamine D1 and glutamate NMDA receptor‐driven mechanisms in the VS play a key role in the pharmacodynamics of EtOH‐induced potentiation of the locomotor effects of MDMA. Abstract : Color‐coded examples of 2‐DG autoradiograms of coronal sections through the striatum of rats given saline, 1.5 g/kg ethanol, 6.6 mg/kg MDMA, or ethanol+MDMA (same doses). Note the increase of grain density in the ventral striatum (white circle) after ethanol+MDMA vs. MDMA, saline or ethanol (which decreased grain density). Administration of MDMA caused transient locomotor hyperactivity. Alcohol administration put rats into a state of transient lethargy. Combining the administration of alcohol with MDMA induced more marked locomotor hyperactivity than when MDMA was administered in the absence of alcohol. This potentiation of the hyperlocomotor effect of MDMA by alcohol was prevented or greatly attenuated by a reversible 'anesthesia' of the ventral striatum (not illustrated) or by a dopaminergic lesion of this structure (not illustrated), as well as by a blocking of dopamine D1 (RD1) receptors or glutamate NMDA receptors (RNMDA) of the ventral striatum. Furthermore, activation of D1 dopamine receptors mimicked the effects of alcohol on MDMA‐induced hyperlocomotion.